PENGARUH METODE DEMONSTRASI BERBANTUAN MEDIA KARTU TERHADAP HASIL BELAJAR SISWAKELAS V SD - Febrianti Siska; Bistari Bistari; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem in this study is "What is the effect of the demonstration method assisted by card media on fraction learning outcomes in class V students of 34 Pontianak City Primary Schools". This study aims to describe the effect of the demonstration method assisted by the media card in the learning of mathematics in fractions of class V 34 Primary School Pontianak City. This study uses an experimental method of Quasi Experimental Design with the Nonequivalent Control Group Design. The population in this study were all fifth grade students of 34 Pontianak Elementary School. The sample in this study was class V B students totaling 34 students as the experimental class, and class V C students totaling 33 students as the control class. Data collection techniques used are direct observation techniques, and measurements. Data collection tools used were observation sheets and test essays. Based on the results of data analysis, the experimental class pre-test average was 61.99 and the experimental class post-test was 79.28. The average of the control class pre-test was 60.61 and the control class post-test was 76.48. From the results of the calculation of Effect Size (ES) of 0.31 including the classification is medium. This shows that the method of demonstration assisted by the media card has a moderate effect on learning outcomes in learning mathematics fraction material in class V 34 Primary Schools Pontianak City.Keywords : Card Media, Demonstration Method, Fraction,Influence, Learning Outcomes.